8 Effects of a Bovine Appeasing Substance Application at Weaning on Temperament and Growth of Bos Indicus Influenced Heifers. (8th October 2021) - Viera, Douglas G; Ranches, Juliana; Vedovatto, Marcelo; Pirota, Giovana G; Cappellozza, Bruno I; Canutoce, Nelson; Pereira, Thais G; Yshiayam, Luís Fernando; Henrique, Thomas; Fernandes, Henrique J
Abstract: The objective of this study was to evaluate the effects of a synthetic analogue of the bovine appeasing pheromone (i.e. bovine appeasing substance; BAS) on growth and temperament of heifers. At weaning (d 0), 30 heifers (Aberdeen Angus ′ Nelore; 8 ± 1 mo) were stratified by body weight (199.8 ± 16 kg) and randomly assigned to receive a single dose of BAS (n = 15; SecureCattle; Nutricorp, Araras, SP, Brazil) or saline (CON; n = 15; saline 0.9% NaCl). Treatments (5 ml) were topically applied to the nuchal skin area of each animal on d0. Body weight was collected on d 0, 6, 15, 45, and 150. Chute score (1 to 5; 1 = calm, no movement; 5 = violent and continuous struggling) and chute entrance and exit score (1 to 3; 1 = slow; 3 = fast) were collected on d 0, 2, 6, 15, 45 and 150. Scores were averaged across 4 trained technicians. Data were analyzed using the MIXED procedure of SAS. Heifers assigned to BAS had greater (P < 0.01) average daily gain (ADG) than heifers assigned to CON treatment from d 6 to 15 (2.35 and 1.88 kg/d ± 0.16) and from d 15 to 45 (1.79 vs. 1.56 kg/d ± 0.08). Heifers assigned to BAS had lower (P < 0.01) chute entrance score on d 6, 15, and 45, and chute exit score on d 2 to 45 (P = 0.05) when compared to heifers assigned to CON. Additionally, heifers assigned to BAS tended (P = 0.08) to have lower chute score, from d 1 to 150 than heifers assigned to CON. The application of BAS at weaning improved heifers ADG, likely due to an improvement in temperament, suggesting that BAS application has calming effects in the beef cattle herd.